2008
DOI: 10.1139/z08-124
|View full text |Cite
|
Sign up to set email alerts
|

Demography of the lizard Sceloporus grammicus: exploring temporal variation in population dynamics

Abstract: We conducted a 5 year demographic study in one population of the viviparous lizard Sceloporus grammicus Wiegmann, 1828 in central México. The population was structured in three size classes (juveniles, small adults, and asymptotic adults) for which we estimated annual survival and fecundity rates. A population projection matrix was constructed for each annual transition. All of them resulted in finite rates of population growth (l) that, although variable from year to year (from 0.808 to 1.065), were not signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 60 publications
0
12
1
1
Order By: Relevance
“…Similarly, Zúñiga-Vega, Méndez-de la Cruz and Cuellar (2008) found that capture probability (p), which is the other parameter that must necessary be estimated when analyzing mark-recapture data, did not differ among stage classes but differed notably across years. Hence, we constrained p to be similar among stage classes and different through time in all our models.…”
Section: Environmental Effeets On Survival and Growth Ratesmentioning
confidence: 92%
See 4 more Smart Citations
“…Similarly, Zúñiga-Vega, Méndez-de la Cruz and Cuellar (2008) found that capture probability (p), which is the other parameter that must necessary be estimated when analyzing mark-recapture data, did not differ among stage classes but differed notably across years. Hence, we constrained p to be similar among stage classes and different through time in all our models.…”
Section: Environmental Effeets On Survival and Growth Ratesmentioning
confidence: 92%
“…A demographic study was previously conducted on this population (Zúñiga-Vega, Méndez-de la Cruz and Cuellar, 2008). In this previous study, mark-recapture data was used to calculate stagespecific survival rates.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations